PENGEMBANGAN INSTRUMEN PENILAIAN SIKAP ILMIAH SAINS SISWA SEKOLAH DASAR (SD) BERBASIS PENDIDIKAN KARAKTER - Ferdinandus Bele Sole; Desak Made Anggraeni (Postgraduate, University of Mataram, 2017)
This study aims to develop scientific science attitudes assessment instruments that can be used in elementary school-based values of character education. This research is a research development (R & D) conducted for one year with preliminary study stage, product development, product trial and product dissemination developed. A preliminary study was conducted by surveying the implementation of the science assessment in primary school. The preliminary study results show that teachers in 10 surveyed schools have never implemented a scientific attitude assessment in science learning. At the stage of product development, has developed a scientific attitude assessment instrument that has been validated by experts. The product trials were conducted in three stages: initial field test, main field test and field operational test. In the initial field test, it was conducted in two schools with 20 respondents in each class. Initial field test results show that the instrument reliability level is good, but there are still some invalid items that are 11 items in class IV, 8 items in class V and 7 items in class VI. This is because there are still some respondents who have not read smoothly so that they have difficulty in answering questions. In the main field test, it was conducted in 8 schools with 91 respondents. The main field test result is that there are 5 invalid questions, both in class IV, V and VI. Operational field tests were carried out with the number of respondents each 13 students from 10 schools. Field operational test results are all items declared valid and reliable. The last stage is to disseminate products through scientific forums such as seminars and socialization to schools. The scientific attitude instruments developed in this study can be used by elementary teachers to assess the scientific attitudes of elementary students.